Synthesis of Indoline-2,3-diones by Radical Coupling of Indolin-2-ones with tert-Butyl Hydroperoxide - Ying, Wei-Wei; Zhu, Wen-Ming; Liang, Hongze; Wei, Wen-Ting (Synlett, 2018)
A novel strategy has been developed for the synthesis of indoline-2,3-diones through a metal-free radical-coupling reaction. Alkyl radicals derived from indolin-2-ones through a radical-transfer reaction combine with the tert-butylhydroperoxy radical readily generated from commercially available tert-butyl hydroperoxide to afford 3-(tert-butylperoxy)indolin-2-one intermediates that can be further transformed into indoline-2,3-diones under air. This strategy provides a simple and eﬃcient route to the construction of a C=O bond without the use of any metal catalyst or base.
Keywords: radical coupling; indolinones; oxidation; indolinediones; tert-butyl hydroperoxide